Ethnomathematics: Concept of Geometry and Cultural Wisdom In The Construction of The Minangkabau Gadang House - Susanti, Eva; Kurniawan, Haris; Widodo, Sri Adi; Perbowo, Krisna Satrio (Universitas Wiralodra, 2023)
This research is one form of effort to show evidence of the relationship between mathematics and culture, especially on the subject of geometry, as well as to show the public that culture has an attachment to mathematics. The purpose of this study was to determine the construction process of the Minangkabau Gadang house and the geometric concepts contained therein. This study used qualitative research methods to describe the rules of cultural wisdom in building Gadang houses and the geometric concepts inside. With literature studies and observations of Gadang houses West Sumatera. The results of this study indicate that the construction of this traditional house turns out to be unwittingly using mathematical concepts to adapt to the environmental conditions in which it was built so that it does not only look at the aesthetics and comfort of living but also the security that the residents of the house get. Of course, it will be different in each regional condition and traditional house.